6. LSM DAN NEGARA (STUD! KOMPARATIF HUBUNGAN LSM DAN NEGARA ERA ORDE BARU DAN PASCA ORDE BARU DALAM MENGGAGAS PEMILU YANG DEMOKRATIS / PEMILU 1999) - Erowati, Dewi (FORUM, 2009)
The NGO (Non Government Organization) and the state, directly or indirectly will always be involved to do interactions in certain relation patterns. Social political growth and changes also bring impacts and effects to the relation pattern forms between them. The recent study was a study of comparative on the relation between the NGO and the state in New Order and Post the New Order. The NGO and state relation in New Order era can be unbalanced relation because the NGO always be follow state of the policy. The NGO and state relation Post the New Order era more resiprocally, in that showed from merger the NGO community to law reformation nationality concorsium (Konsorsium Reformasi Hukum nasional). Such that, the NGO movement more sistematic and impact from the state policy.